Assessment of the value of therapeutic monitoring of tacrine in Alzheimer's disease. - Roberts, C; Ford, J; Truman, C; Scott, M; Mäkelä, P; Wilcock, G (1998)
OBJECTIVES: The purpose of this study was to validate the lower end of the putative therapeutic range of serum tacrine concentrations of 7-20 ng ml(-1) in the treatment of Alzheimer's disease. METHODS: The relationship between dose, steady-state serum tacrine concentrations and change in MMSE score (a measure of cognitive function) was examined in 106 Alzheimer's disease patients who had been treated with the drug for 12 weeks. RESULTS: In all, 72% of patients showed some response, but there was no relationship between dose and the chance of a favourable outcome. The proportion of patients with serum concentrations above 7 ng x ml(-1) who improved (79%) was significantly greater than that of those with serum concentrations below this level (47%) (P < 0.02). Also, a significantly greater proportion of patients with serum concentrations above both 5 ng x ml(-1) and 9 ng x ml(-1) showed improvement in comparison to those with concentrations below these levels. CONCLUSIONS: This study indicates that therapeutic monitoring of serum tacrine concentrations might increase the possibility of responding to tacrine by some 68%. This represents an important contribution to the management of Alzheimer's disease patients with this drug, and may also be relevant to the use of the newer generation of cholinesterase inhibitors.